Ground Motion Response Analysis of High Arch Dam Considering Traveling Wave Effect - LI Jing; ZHU Mingxiang; XING Jianying; CHEN Jianyun (Renmin Zhujiang)
The seismic performance assessment of a 300-m-level high arch dam has generally adopted an analysis model based on the dynamic interaction between the dam body and the foundation. However, the horizontal spatial scale of the ground motion input boundary at the bottom of the analysis model including the foundation can reach several kilometers, with a large spatial span. The non-uniformity of ground motion on the horizontal external boundary of the model should not be ignored, especially under near-fault ground motion. To study the influence of the uniform ground motion input of the external boundary on the dynamic response of the arch dam, this paper takes a certain 270-m-level high arch dam as an example and adopts the ETA method to analyze the influence of the uniform input and the non-uniform input considering the traveling wave effect on the displacement, stress, and damage response of arch dam. It is found that, compared with the stress response results of the arch dam obtained by uniform input, the maximum arch stress in some areas of the arch dam stress response considering the traveling wave effect increases, while the maximum beam stress decreases, and the stress on the input side of the ground motion increases significantly. Compared with the uniform input, the damage response law of the dam with traveling wave effect is mainly that the damage to the dam face is reduced, while the damage to the arch end and the dam bottom increases. From the maximum displacement of the dam top relative to the dam bottom, it can be seen that the traveling wave input increases the dam top displacement significantly relative to the uniform input. From the spatial point of view, the dam top displacement near the left bank increases significantly upstream, the dam top displacement decreases as it moves to the right bank, and the dam top displacement near the right bank increases significantly downstream.